Concepções de síntese no estudo deleuzeano de Hume - Cardoso Júnior, Hélio Rebello [UNESP]; Vargas, Gonzalo Montenegro [UNESP] (My University, 2014)
In order to emphasize the leading role Hume plays in the work of Deleuze, especially in his philosophical production during the years 1950 and 1960, we will describe the main concepts of synthesis the French philosopher proposed in Empiricism and Subjectivity , in 1953. One of the questions that stimulate this research is the empirical origin of the self. Deleuze thinks this origin as being started by a sort of incomprehensible or empirical synthesis. Furthermore, we recognize the synthesis of time which describes the condition governing the operation of habit. There are at least two other concepts of syntheses in Deleuze s book dedicated to Hume. We find, on one hand, the synthesis indicating the agreement of the faculties or, to state it clearly, the agreement between the principles of association and of passion. On the other hand, we still find the syntheses of judgments arising from the correlation between the faculties.

Com o intuito de salientar o lugar que a leitura de Hume tem dentro da obra de Deleuze, notadamente durante sua produção filosófica dos anos 1950 e 1960, interessa-nos descrever as principais concepções de síntese que o francês propõe em “Empirismo e subjetividade”, de 1953. Uma das questões que motivam essa pesquisa é a origem empírica do eu. Trata-se do que Deleuze denomina síntese incompreensível ou empírica. Ademais, reconhecemos a síntese do tempo na qual se descreve a condição que governa o funcionamento do hábito. Às sínteses anteriores, adicionam-se pelo menos mais duas identificadas nessa obra. Temos, de um lado, a síntese que indica o acordo das faculdades ou, mais exatamente, da articulação entre os princípios de associação e os da paixão, e, de outro, a síntese dos juízos, que surge da correlação entre as ditas faculdades.
Conceptions of synthesis according to Deleuze's study on Hume
Keywords: Deleuze; Hume; Synthesis; Habit; Faculty; Judgement; Deleuze; Hume; Síntese; Hábito; Faculdade; Juízo